O processo de construção do plano diretor no planejamento universitário da UFAL Campus Arapiraca: um estudo de caso - Ferreira, Dayana Alves (2019)
This dissertation is being published in a Federal Higher Education in order to discuss the elaboration of the Master Plan of a Higher Education Institution. The chosen locus was the Arapiraca Campus of the Federal University of Alagoas (hereinafter UFAL). The objective was to develop and analyze the federal higher education rules as the Master Plan in the training plan of the Campus of Arapiraca from Ufal to evaluate its implementation process. The academic and social strategy of the research was driven by the fact that the Master Plan as a new initiative has evolved into an additional process. Theoretically, we are basing our discussion on the works of Pereira (2010), Matos (1999), Drucker (1998), Mintzberg, Ahlstrand and Lampel (2000), Hamel and Prahalad (2000), Cunha (1996), Herman and Watters (2002), Kerzner (2009), Putnam (2008), Antunes and Gonçalves (2010), Lizote (2013), Kerr (1982), Baldridge (1982), Lang (1990) and Porter (2001). The means of investigation, as well as the studies adopted, were researched at the documentary level, where a case study of descriptions and demonstrations of documents by documents was necessary. It was concluded that old problems remain in the management of the University. The process of implementation of the Arapiraca Administration Plan was successful in its implementation and in the control of operations of the administrative processes.